(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Centrifugal devices are of huge workability due to their method of operation. However their performance is a major problem which involves periodic checking and maintenance. This paper is review on centrifugal device e such as blower and their types. Optimization technique such as Taguchi is used by most of the scholars previously in identifying optimum configurations for centrifugal devices. Further it is found that analytical approach is applied for analysing the working parameters such as using CFD tools which provides fast and accurate results.